2018
DOI: 10.1038/s41401-018-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Icariin prevents bone loss by inhibiting bone resorption and stabilizing bone biological apatite in a hindlimb suspension rodent model

Abstract: Bone loss induced by microgravity is a substantial barrier to humans in long-term spaceflight. Recent studies have revealed that icariin (ICA) can attenuate osteoporosis in postmenopausal women and ovariectomized rats. However, whether ICA can protect against microgravity-induced bone loss remains unknown. In this study, the effects of ICA on a hindlimb suspension rodent model were investigated. Two-month-old female Wistar rats were hindlimb suspended and treated with ICA (25 mg·kg·d, i.g.) or a vehicle for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Here, we found a great ability of ICA administration to improve the micro-architecture of bone trabecula and increase BMD and BV/TV in OVX rats ( Figure 1 ), in accordance with the recent studies from Wei et al ( 14 ) and Zhou et al ( 16 ). A significant decrease of BGP and RANK and increase of OPG in OVX rat serum suggested a direct evidence of ICA-induced osteogenic differentiation ( 38 ), which was probably mediated via Wnt/β-catenin pathway like other TCMs such as radix Salviae miltiorrhizae (RSM) and Liuwei Dihuang ( 10 , 13 , 39 , 40 ). Other signaling pathways including IGF-I coupled non-genomic ERα and STAT associated with ICA-induced OP improvement have also been documented ( 16 , 17 ), but whether the pathways RANKL/RANK/TRAF6 and OPG/RANKL/cathepsin K identified in other TCMs ( 39 , 41 ) can be activated by ICA still warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found a great ability of ICA administration to improve the micro-architecture of bone trabecula and increase BMD and BV/TV in OVX rats ( Figure 1 ), in accordance with the recent studies from Wei et al ( 14 ) and Zhou et al ( 16 ). A significant decrease of BGP and RANK and increase of OPG in OVX rat serum suggested a direct evidence of ICA-induced osteogenic differentiation ( 38 ), which was probably mediated via Wnt/β-catenin pathway like other TCMs such as radix Salviae miltiorrhizae (RSM) and Liuwei Dihuang ( 10 , 13 , 39 , 40 ). Other signaling pathways including IGF-I coupled non-genomic ERα and STAT associated with ICA-induced OP improvement have also been documented ( 16 , 17 ), but whether the pathways RANKL/RANK/TRAF6 and OPG/RANKL/cathepsin K identified in other TCMs ( 39 , 41 ) can be activated by ICA still warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Bone strength plays a key role in maintaining bone health, including bone density, architecture, mineralization, and load tolerance of both cortical and trabecular bone area. [ 36,37 ] Although BMD is an essential factor of bone strength, it cannot be held accountable for the architectural changes occurring in trabecular bone. [ 38,39 ] The assessment of both BMD and bone biomechanical properties may improve the estimation of bone strength.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing interest has risen for the treatment of intractable bone diseases with traditional Chinese medicine (TCM) 14 . Our previous studies have indicated that muscone, cordycepin and osthole have beneficial effects for ONFH 15‐17 .…”
Section: Introductionmentioning
confidence: 99%